A COMPARATIVE ANALYSIS OF THE MALE SETTING IN THE FIGHT CLUB AND A MAN ASLEEP / DÖVÜŞ KULÜBÜ VE BİR ADAM UYKUDA ESERLERİNDE ERKEK ALANININ KARŞILAŞTIRMALI OLARAK İNCELENMESİ - Esin KUMLU (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi, 2016)
The twentieth century postmodern world not only created an era of a decentered way of life but also tremendously triggered a decentered literary style that somehow achieves to encompass the entire story of human life. Although the term postmodern seems to be a broad concept that has different effects in different geographies, it magically succeeds to unite differences and reflect a common story behind a veil. Chuck Palahniuk’s The Fight Club (1999) and George Perec’s A Man Asleep (1967) are marvelous examples for that. While Palahniuk’s story is the voice of the reflections of postmodern human life in the United States, therefore American postmodern literature, Perec’s story becomes the voice of postmodern human life in France. Although two works signify different geographies, a comparative analysis of these works highlight the reality that two different cultures are bounded with each other in terms of the literary concepts; ‘daily life;’ ‘sleep,’ ‘headache – pain,’ ‘depression,’ ‘addiction,’ ‘the double’ and ‘the notion of success.’ Perec’s and Palahniuk’s nameless characters’ lives surrounded by cultural codes of abundance at first sight, which later became their captivity that triggers either depression or schizophrenia. At this point, a comparative analysis that acts as a bridge between two different cultures and geographies postulate the idea that in the postmodern world of fragmentation, comparative literature achieves to form a web of wholeness which helps the reader to develop a cultural, historical, social and psychological analysis of stories which are the stories of all of us.